A Summary of the Research on Feedback-seeking Behavior - Pang, Kailun (Transactions on Economics, Business and Management Research, 2024)
Feedback seeking behavior of employees plays an important role in the development and progress of an organization. Among the influencing factors of feedback seeking behavior, leadership style has attracted the attention of researchers. In this study, the connotation, motivation and related research of feedback seeking behavior are sorted out. It can be found that the characteristics of feedback seekers, the characteristics of feedback sources and organizational environment factors may affect feedback seeking behavior. In a working environment full of positive interpersonal relationships, employees will be more willing to seek feedback actively.